STANDALONE AVR PROGRAMMER - Wiedjaja, Wiedjaja; Saputra, Hendra Tejo; Utama, Indra Buana; Setiawan, Rinaldo Yotanto (Bina Nusantara University, 2007)
Article clarifies a research having goals to make AVR programming system that is portable, by makingsystem modul based on AVR AT8535 as AVR Programmer/Master and AT8515 asAVR Socket. The module instructionat first is hex file was sending from PC to AVR Programmer/Master that later will be saved to external memory. Afterthe hex file saved, programming process will not need help from PC anymore. The saved hex file that saved toexternal memory can be choosen that later will be written to AVR Socket. So, the AVR program can be donerepeatedly as long as data on external memory still saved. The standalone that was made can only programed AVRATMega 8515L. From the research ita can be conluded that on case of repeated program, Stand Alone AVR able tosave time 20% more faster that programming using AVR codevision.